Rare earth elements, iron and manganese in ochre-precipitates and wetland soils of a passive treatment system for acid mine drainage - Prudêncio, M. I. (2017)
The rare earth elements (REE) along with iron and manganese distribution in ochre-precipitates and wetland soils in a passive system for acid mine drainage treatment (Jales, Portugal) was studied. The results obtained by instrumental neutron activation analysis showed a higher incorporation of the light REE (particularly La and Ce) by the ochre-precipitates resulting from the mine water-limestone interaction. These fluffy materials influence the entrance of the first wetland where a correlation between Fe and La and Ce was found. Then Mn phases appear to play a more important role controlling REE distribution in the remaining area of the wetland soils.